An extracellular matrix extract for tissue-engineered cartilage. - Lum, L.Y.
Cartrigel modulates the chondrogenic effect of TGF-β3 on mesenchymal stem cells in photopolymerizing hydrogels. Tissue engineering of cartilage in photopolymerizing PEG-based scaffolds may benefit from the incorporation of ECM extracts for greater control of cell behavior.
Keywords: Cartilage; Cell behavior; Photopolymerizing PEG-based scaffolds; Tissue engineering